(Ir)regular Mood Swings: Lexical Variability in Heritage Speakers' Oral Production of Subjunctive Mood. Issue 2 (15th February 2022) - Giancaspro, David; Perez‐Cortes, Silvia; Higdon, Josh
Abstract: Previous research indicates that heritage speakers (HSs) of Spanish produce both subjunctive and indicative mood in expected subjunctive contexts. The present study sheds new light on this pattern by testing the effects of morphological regularity on HSs' mood production in volitional contexts, where Spanish‐dominant speakers (e.g., first‐generation immigrants) use almost exclusively subjunctive forms. Results of an elicited production task, completed by 42 HSs and 10 first‐generation controls, reveal that HSs differentiate between the two moods. Despite this sensitivity, HSs also exhibit variability, which is strongly conditioned by regularity. Whereas HSs produce subjunctive forms almost categorically with irregular verbs, their subjunctive production with regular verbs is more variable, a pattern we link to irregular verbs' higher relative lexical autonomy and perceptual salience. Instead of classifying HSs' morphological knowledge in binary terms, we argue for the importance of exploring how variability with mood is shaped by the morphological characteristics of individual lexical items. Abstract :